Peningkatan Aktivitas dan Hasil Belajar Sejarah Melalui Penerapan Metode Pembelajaran Kooperatif Tipe Talking Stick pada Siswa Kelas X-1 SMA Muhammadiyah 3 Jember - Moh Imron Rosidi (Universitas Negeri Yogyakarta, 2016)
ClassX-1 at SMAMuhammadiyah 3 Jember less interested join in the lessons of history a look at teaching history took place. To overcome these problems is to use learning methodthat are tailored to the characteristics of students, where the characteristics of the class X-1 at SMA Muhammadiyah 3 Jember less interested in participating in learning history, students are quickly saturated in receiving lessons, students have a weak memory, and students lazy in reading the lessons material. Learning methodin accordance with the conditions of class X-1, especially in the subjects of history is a type of cooperative learning method Talking Stick. The results obtained in this research can be seen from the percentage of learning activities and student learning results. Student learning activities in the pre cycle 61.11%, 70.83% first cycle reached, and the second cycle the percentage of student activity reached 85.76%. Mastery of student learning results in the cognitive aspects of pre cycle 68.75%, affective and psychomotor aspects are not obtained, completeness student learning results at the first cycle 75% cognitive, affective aspects of 78.12%, and psychomotor aspects 75%, while the mastery of learning results second cycle of 87.5% on the cognitive, affective aspects of 90.62%, 87.5% and psychomotor aspects. Based on the above indicates an increase in the percentage of mastery learning activities and learning results among students in the classical precycle, the first cycle and second cycle. Keywords: cooperative learning method, Talking Stick, learning activities,learning results